Legal Review of the Death Penalty in the Perspective of Human Rights - Putera, Airlangga; Jannah, Miftahul; Nasution, Hanry Setiawan (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
This study aims to determine the regulation of the death penalty in Indonesia and its impact on human rights. The research uses library research and documentation to collect data. The regulation of the death penalty in Indonesia is contained in the Criminal Code legislation and outside it. Statistical data and criminology experts’ hypothesis suggest that the death penalty in Indonesia does not provide a deterrent effect to reduce crime rates. Furthermore, the death penalty violates the convict’s right to life. The right to life is guaranteed in several human rights instruments, including the Universal Declaration of Human Rights, the International Covenant on Civil and Political Rights, the American Convention on Human Rights, Law No. 39 of 1999 on Human Rights, and the Charter of Fundamental Rights of the European Union. The right to life is also guaranteed in the Supreme Constitution of Indonesia, specifically Article 28i of the 1945 Constitution. In Islamic law, the death penalty (qishash) is a legal practice that existed pre-Islamic and was modified during Islamic times.